The Federal Budget : Politics, Policy, Process - Schick, Allen (Book collections on Project MUSE., 2000)
"This revised and significantly expanded edition of The Federal Budget concerns the politics and processes of federal budgeting and the policies that emerge from them. It describes how budgeting works at each stage of executive and legislative action - from preparation of the president's budget through the appropriation and expenditure of funds - and assesses the impact of budget rules on policy decisions. In addition to vital statistics and extracts from important documents, the book also features case studies that dramatize contemporary budgetary politics, providing readers with a "you are there" appreciation of how budgeting decisions are made in Washington."--Jacket.